Differences in Utilization of Lower Limb Muscle Power in Squat Jump With Positive and Negative Load - Fàbrica, Carlos Gabriel; Ferraro, Damian; Mercado-Palomino, Elia; Molina-Molina, Alejandro; Chirosa-Rios, Ignacio (Frontiers in Physiology, 2020)
Jump performance is related to the ability of lower limb muscles to produce power during the push-off phase. However, it is not known if the power associated with the action of active and passive elements of the lower limb muscles change significantly in jumps with positive and negative loads. In this study, the power associated with the action of passive and active components of lower limb muscles as a whole in squat jumps (SJ) with increase and decrease in the external load is analyzed Fourteen trained male subjects (22.5 ± 2.1 years; 176.5 ± 5.4 cm; 75.8 ± 5.8 kg; BMI 24.3 ± 1.8) performed SJ on a force plate. A functional electromechanical dynamometer (FEMD) system was used to change the external load in a range of −30 to +30% of the subject’s body weight. A model comprising a mass, a spring, an active element, and a damper was used. We applied an optimization principle to determine power in center of mass (CoM) (ptot), the powers associated with active element (pact), damper (pƔ), and spring (pk) during the push-off phase. Significant differences between loading conditions for each variable were tested by repeated-measures one-way ANOVA with Bonferroni post hoc analysis, p < 0.05. Shapes of the average curves for instantaneous variation of pact, pƔ, pk, and ptot during push-off with positive loads were closer to 0% than with negative loads. As the load increased, maximum values of ptot, pƔ, and pk decreased. Only with a negative load of −30% did ptot increase significantly, this was not accompanied by changes in pact, pƔ, and pk. The load of one’s own body provides conditions for develop high pact peaks, although the maximum ptot is not achieved in that condition. The increase in negative loads produces a significant increase in ptot, but not in pact and can be interpreted as a situation in which the power delivered to the system by the action of active components is better used. The SJ with positive load, although more similar to the instantaneous changes that occur to the SJ with body weight are not gestures where high power is developed.